Manipulating and visualizing the dynamic aggregation-induced emission within a confined quartz nanopore - Yi-Lun Ying (Nature Portfolio, 2018)
The difficulty in recovering the aggregation-induced emission fluorogens (AIEgens) to the initial dispersed state upon illuminating has limited their applications. Here, the authors employ the confined space in the quartz nanopore to achieve a nanopore-size dependent restriction of AIEgens.